Relationship between director management and the external user satisfaction in health centers in a district of Ecuador - Arbeláez, Gloria (2017)
Introduction: Health management, competence and policy conduction, has exercised with medical prominence. The change in approach evolved to focus their actions on the external user to achieve their satisfaction. Independent studies on management and satisfaction visualized different effects of organizations, managers and users results. It is relevant to prioritize critical nodes between its dimensions in order to develop projects of continuous improvement. Objective: To establish the relationship between the director management and the external user satisfaction. Design: Cross-sectional, correlation study. Setting: District 17D09, Ecuador. Participants: Nine directors of health centers and 652 external users. Interventions: Simple random sampling, expert judgment, validated forms: satisfaction modified SERVQUAL, and management EVAL O1-MRL, informed consent, SPSS V20 analysis, Excel software. Main outcome measure: Director´s Management Index. Results: Director’s management was of regular level in 56% and satisfactory in 44%. External user dissatisfaction was moderate in 89% and mild in 11%. The institutional care was of poor quality in 100%. The level of dimensional correlation was varied between management and dissatisfaction: weak negative (-0.28 and -016), weak positive (0.31) and strong negative (-0.52 and -070). Conclusions: There was a direct and significant correlation between poor management and patient dissatisfaction.